Conventionally fractionated radiation therapy versus stereotactic body radiation therapy for locally advanced pancreatic cancer (CRiSP): An international systematic review and meta‐analysis. Issue 10 (3rd March 2020) - Tchelebi, Leila T.; Lehrer, Eric J.; Trifiletti, Daniel M.; Sharma, Navesh K.; Gusani, Niraj J.; Crane, Christopher H.; Zaorsky, Nicholas G.
Abstract : Background: The goal of this study was to characterize the efficacy and safety of stereotactic body radiation therapy (SBRT) versus conventionally fractionated radiation therapy with concurrent chemotherapy (CFRT) for the definitive treatment of locally advanced pancreatic cancer. The primary outcome measure was efficacy, defined by 2‐year overall survival (OS). Secondary outcomes were incidence of any grade 3/4 toxicity and 1‐year OS. Methods: A PICOS/PRISMA/MOOSE selection protocol was used to identify eligible studies. Inclusion criteria were: 1) patients diagnosed with locally advanced N0‐1 M0 pancreatic cancer; 2) CFRT 1.8 to 2.0 Gy/fraction with chemotherapy per protocol or SBRT ≥5 Gy/fraction in ≤5 fractions; 3) either no control group or another definitive chemotherapy or radiation therapy arm; 4) at least 1 of the outcome measures reported; and 5) single or multi‐arm phase 2/3 prospective study for CFRT and/or phase 1/2 or retrospective study for SBRT. Neoadjuvant and/or adjuvant chemotherapy was prescribed per protocol specifications. Weighted random effects meta‐analyses were conducted using the DerSimonian and Laird method to characterize summary effect sizes for each outcome. Results: A total of 470 studies were initially screened; of these, 9 studies assessed SBRT and 11 studies assessed CFRT. For SBRT, the median dose was 30 Gy, and the most common regimen was 30 Gy/5 fractions. For CFRT, doses ranged from 45 to 54 Gy in 1.8‐ to 2.0‐Gy fractions, with the majority of studies delivering 50.4 Gy in 28 fractions with concurrent gemcitabine. The random effects estimate for 2‐year OS was 26.9% (95% CI, 20.6%‐33.6%) for SBRT versus 13.7% (95% CI, 8.9%‐19.3%) for CFRT and was statistically significant in favor of SBRT. The random effects estimate for 1‐year OS was 53.7% (95% CI, 39.3%‐67.9%) for SBRT versus 49.3% (95% CI, 39.3%‐59.4%) for CFRT, and was not statistically significant. The random effects estimate for acute grade 3/4 toxicity was 5.6% (95% CI, 0.0%‐20.0%) for SBRT versus 37.7% (95% CI, 24.0%‐52.5%) for CFRT and was statistically significant in favor of SBRT. The random effects estimate for late grade 3/4 toxicity was 9.0% for SBRT (95% CI, 3.3%‐17.1%) versus 10.1% (95% CI, 1.8%‐23.8%) for CFRT, which was not statistically significant. Conclusion: These results suggest that SBRT for LAPC may result in a modest improvement in 2‐year OS with decreased rates of acute grade 3/4 toxicity and no change in 1‐year‐OS or late toxicity. Further study into the use of stereotactic body radiation therapy for these patients is needed. Abstract : Stereotactic body radiation therapy may confer a modest survival benefit over conventionally fractionated radiation therapy for patients who have locally advanced unresectable pancreatic cancer with a lower rate of acute toxicity. This study is hypothesis‐generating and serves as a benchmark for further study into the use of stereotactic radiation therapy for unresectable pancreatic cancer.